Basic Training Management Of Civil Servants In Improving The Work Achievement Of PNS In West Java Province BPSDM - Lilis Mulyani Setiasari; Hanafiah; N. Dede Khoeriyah; Agus Mulyanto (International Journal of Social Science, Education, Communication and Economics (SINOMICS JOURNAL), 2022)
This research is motivated by the performance problems of Civil Servants, namely performance targets that are not achieved, dishonest behavior, and other events that are not as expected resulting in the low quality of performance of Civil Servants (PNS). This research approach is a qualitative research with case study method. The results of this study indicate that basic training planning is made with reference to the RPJMD and the Strategic Plan. The organization is regulated by the mechanism of division of tasks, regulated based on the Decree of the Head relating to the Organizational Structure of the training management program which is generally understood and implemented by BKPSDM. The implementation of education and training at BKPSDM was carried out well, in addition to providing quality training for trainees, the committee also paid great attention to the health of participants. Supervision of basic training is carried out daily by class observers during distance learning, while classical supervision is carried out by the tutor. Barriers in general are due to the large number of participants while the time for CPNS is only one year so that there is extraordinary activity on the part of the organizers and facilitators. In overcoming the obstacles to the shortage of learning media, namely socialization before the implementation of careful preparation from the organizers and assessors of work performance. Submission of information through socialization and letters as well as utilizing the head of the class.